GUBUK ZISWAF: SOLUSI PEMBIAYAAN HIDUP MASYARAKAT BERBASIS PEMBERDAYAAN LOKAL DI TENGAH PANDEMI COVID-19 - Prahoro Yudo Purwono; Fikky Ardiansyah; Syahrul Gunawan (Jurnal Ekonomi Rabbani, 2021)
The COVID-19 outbreak has the potential to change the economic situation which is marked by a change in the trade map, in addition to causing the cessation of various business fields, global trade performance will certainly be disrupted due to the slow improvement in manufacturing performance. On the other hand, the problem of distributing ZISWAF funds (Zakat, Infaq, Shadaqah and Waqaf) has not been evenly distributed. Therefore, Gubuk ZISWAF is proposed. The purpose of this research is to describe the concept and implementation of Gubuk ZISWAF as a solution for community living financing scheme based on local empowerment during the COVID-19 pandemic. The research method used is qualitative research with literature review approach. The result shows that the implementation technique  will be carried out to realize the Gubuk ZISWAF starts from the planning stage, where is related to the formulation of policies by the government and collaboration with related parties, then continued with research and coordination between related parties and the government, development stage, socialization program, and comprehensive implementation (with a ball pick-up system). The results of the implementation of the Gubuk ZISWAF in each of these villages have had a positive impact on the Indonesian economy. In addition to suppressing the rate of poverty in the midst of a pandemic, the possibility of social crimes and the stalling of the economy as well as the spread of COVID-19 can also be prevented.